Public-private partnerships in new EU member countries of Central and Eastern Europe: An economic analysis with case studies from the highway sector - Andreas Brenck; Torsten Beckers; Maria Heinrich; Christian R. von Hirschhausen (EIB Papers, 2005)
This paper analyses the role of public-private partnerships (PPPs) for infrastructure development in the new EU member states and candidate countries in Central and Eastern Europe. We survey projects in transport, water, energy, and telecommunications sectors and then focus on the highway sector. Based on theoretical considerations and extensive fieldwork in Hungary, Poland, Croatia, and the Czech Republic, we find that PPPs have not been very successful in the region to date. This is mainly due to the unfavourable institutional environment during the transition period, suboptimal project design, and unrealistic demand projections. However, the conditions for successful PPPs have considerably improved, partly due to EU membership, so that PPPs remain an important option for the second generation of infrastructure projects.
Keywords: 330; Public-Private Partnership; Autobahn; Straßenbaufinanzierung; EU-Staaten (Osteuropa)